Nitrogen in the soil - Donaven, Ernest A. (My University, 1894)
Introduction: The soil to the agriculturist is the decomposed rock of the geologist, usually with other material, the product of life, intermingled with it. It is the loose porous coating, covering the earth wherever plant life is found. According to its position, soil is divided into two great classes. 1” sedimentary or that remaining on the flat tops of mountains, where it is formed, and 2” transported. It is of the economic soils that we shall deal, they, being, by far the most economic interest. Erosion, or rock wearing, is caused by changing temperature, moving ice and water and the chemical action of air, water, and plant and animal residues. The water then takes it up and rolls or carries it off down the hills to lower level, where the movement is less rapid and the soil particles are deposited. On the way down the pieces are worn round and ground fine. Parts of other rocks are mixed in, and by the time it is deposited in the river valleys, it is a pulverized, palpable, conglomerate mass of rock dust. For years it has been covered with a grass and forest growth. Wild beasts seek food and shelter in its depths, and the birds of the air live among its branches.
Citation: Donaven, Ernest A. Nitrogen in the soil. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Geology; Erosion; Nitrogen; Soil; Agriculture; Theses; Manuscripts (documents)